Occurrence of red blood cell abnormalities in donor blood donated at the regional blood transfusion centre, Mombasa, Kenya - Nyarambe Wigina1Ronald; Njoki, Kaggia, Serah; Ngugi Kahato, Michael; Mzee Said, Suleiman; Tunje Jeza, Victor; Bundi Gichangi, Peter (Multidisciplinary Journal of Technical University of Mombasa, 2023)
During transfusion, components of blood including red blood cells, platelets and plasma are directly administered into the recipient to treat conditions such as anaemia and haemostatic deficiencies. In most cases, effective blood transfusions will positively impact patient prognosis. Red blood cell abnormalities greatly impact on the effectiveness of blood transfusion. This is because the efficacy of a red blood cell unit depends on the amount of blood delivered, the quality of cells and the life span of a given unit. The aim of this study was to establish the occurrence of red cell abnormalities in donor blood. This descriptive cross-sectional study was done at the regional blood transfusion centre, Mombasa and at the Technical University of Mombasa, Kenya. Consecutive blood samples were analyzed for selected red cell parameters. A total of 676 samples were analyzed. The study found that 31.07 % of the donor samples had one or more of the abnormalities assayed. There was a significant variation (t - 0.03, CI 95%) in the total red blood cell count. A significant Pearson’s positive correlation was realized between the osmotic fragility and haemoglobin concentration (r = 0.195; p < 0.001). This shows that a significant proportion of donated red blood cells in the donor pool had intrinsic or extrinsic abnormalities. There is therefore need to develop strategies that may better help to filter out these abnormalities as well as investigate the effect of such abnormalities to the recipient.